THE EVALUATION OF THE IMPLEMENTATION OF PERFORMANCE ACCOUNTABILITY SYSTEM IN THE ASSEMBLY OF POHUWATO REGENCY - Titin Dunggio; Rizal; Fidi Mustafa (Governance: Jurnal Ilmu Administrasi Publik, 2021)
The present study aims to: (1) determine the evaluation of the implementation of the performance accountability system in the assembly of Pohuwato Regency. (2) Determine the supporting and inhibiting factors of the implementation of the performance accountability system in the assembly of Pohuwato Regency. This study used a qualitative descriptive approach through observation, in-depth interviews and documentation in collecting the data. Moreover, the data analysis technique was carried out through three stages namely data reduction, data presentation, and conclusion. As the results, the current study shows that: 1) the evaluation of the implementation of the performance accountability system in the assembly of Pohuwato Regency has not been going well. It can be seen from three aspects. First, planning.The formulation does not involve the sections and sub-sections. Each stage is not accompanied by supporting documents and is not published on the official website. Second, the process of monitoring and observing which is the implementation of its main tasks and functions has not been implemented optimally, therefore, the agreed performance targets have not been used to measure the success of achieving performance. Third, evaluation indicating that the performance indicators that do not fully meet the SMART criteria, weak monitoring, and no action plan document, no SOP work mechanism and data improvement. 2). in implementing the performance accountability system in the assembly of Pohuwato Regency, there are 2 supporting factors, namely infrastructure and budget. However, there are three inhibiting factors, namely leadership, where the low and middle managers tend to ignore the aspects of administrative responsibility. In addition, the leading Managers also lack focus and consistency in monitoring the implementation of the performance accountability system. In relation to human resources, most of the quality and understanding of civil servants on their main duties and functions are still low and they are not responsible for the assigned task. Management Control Methods and Policies have not been implemented a hierarchical system or procedure. There is no SOP including performance data management, so in general, the work system has not been distributed properly and evenly.